2018
DOI: 10.13152/ijrvet.5.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Value of CPD Activities Among VET Teachers

Abstract: Context: Teachers in vocational education and training (VET teachers) have specific conditions for their continuing professional development (CPD). They have a background in an initial occupation, in which they now teach and train the next generation. Thus, as VET teachers, they are expected to master the knowledge and skills of that occupation, even if they have now crossed the boundary from the community of their initial occupation to the community of the school. This study explores the perceived values amon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…However, this is not to say that VET teachers do not need organised CPD initiatives, but rather that this seems to be rare in Swedish VET. This means that VET teachers' CPD depends on individual initiatives and drivers (Andersson, Hellgren, and Köpsén 2018), rather than being part of a strategy for the institution. A strategy for developing VET teachers' CPD should include the responsibility of the institution to organise learning at work as well as CPD activities, but also to encourage individual initiatives and a passion for the occupation (Broad 2013).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, this is not to say that VET teachers do not need organised CPD initiatives, but rather that this seems to be rare in Swedish VET. This means that VET teachers' CPD depends on individual initiatives and drivers (Andersson, Hellgren, and Köpsén 2018), rather than being part of a strategy for the institution. A strategy for developing VET teachers' CPD should include the responsibility of the institution to organise learning at work as well as CPD activities, but also to encourage individual initiatives and a passion for the occupation (Broad 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These studies raised new questions, resulting in a survey study of participation in various CPD activities among VET teachers (Andersson, Hellgren, and Köpsén 2018;. It showed that reading was the most common CPD activity (cf.…”
Section: Vet Teachers' Cpd In the Initial Occupation And Their Dual Imentioning
confidence: 99%
See 3 more Smart Citations